Sections filled with trees, people, joy and giants - Prats, Eva
La autora analiza la obra del arquitecto español Enric Miralles.
Keywords: MIRALLES, ENRIC; ARQUITECTOS; TRAYECTORIA PROFESIONAL; TEORIA; CRITICA